LabelBoost: An Ensemble Model for Ground Truth Inference Using Boosted Trees - Faridani, Siamak; Buscher, Georg (Proceedings of the AAAI Conference on Human Computation and Crowdsourcing, 2013)
We introduce LabelBoost, an ensemble model that utilizes various label aggregation algorithms to build a higher precision algorithm. We compare this algorithm with majority vote, GLAD and an Expectation Maximization model on a publicly available dataset. The results suggest that by building an ensemble model, one can achieve higher precision value for aggregating crowd-sourced labels for an item. These higher values are shown to be statistically significant.